Effect of water supply on nutrient transport in grapevine varieties - Miklós, E.; Hajdu, E.; Ésik, É.; Gábor, Gy.; Váradi, Gy. (International Journal of Horticultural Science, 2000)
The effect of water supply on availability of macro nutrient elements (N, P, K) by the plants in the soil and their transport in the plants were examined. In a field experiment two grapevine varieties characterized by higher (White Riesling B 7) and lower (Kövidinka K 8) water requirement were compared on the basis of N, P, K concentrations of leaf blades, petioles and berries. A different water supply of the vineyard was achived by striped coverage of the soil with plastic foil to exclude rainfalls from the beginning of May to ripening. Humidity of the soil decreased as the vegetative phase advanced. Soil cover resulted in 25-30% decrease of the water content in the soil at flowering but this difference gradually disappeared till veraison (i.e. the start of intense growth of the berries). The water consumption in the White Riesling B 7 plantation was more intensive. Mobility and availability of N, P, K in the soil was restricted by water exclusion (i.e. plastic soil cover) at flowering. Nitrogen was slightly affected, whereas P and K were in a higher extent. Comparing the transport of nutrient elements in the two varieties, leaf blades of Kövidinka K 8 contained less N and more P and K than White Riesling B 7 at flowering and more N and P and less K at ripening. Water deficiency inhibited K accumulation in the berries of White Riesling B 7, while this effect did not appear in Kövidinka K 8.Water exclusion decreased the yield of White Riesling B 7 already at lower bud loading, the yield of Kövidinka K 8 was affected only at higher bud loading. The higher yields of the treatments in Kövidinka K 8 plantation support the superior performance of this variety under the hot and dry climate of the Hungarian Great Plain.